The Arabidopsis thaliana trehalose-6-phosphate phosphatase gene AtTPPI regulates primary root growth and lateral root elongation - Lin, Qingfang; Gong, Jiaxin; Zhang, Zhiliang; Meng, Zizi; Wang, Jianyong; Wang, Song; Sun, Jing; Gu, Xu; Jin, Yuting; Wu, Tong; yan, Nuo; Wang, Yuxin; et al. (Frontiers in Plant Science, 2023)
Roots are the main organs through which plants absorb water and nutrients. As the key phytohormone involved in root growth, auxin functions in plant environmental responses by modulating auxin synthesis, distribution and polar transport. The Arabidopsis thaliana trehalose-6-phosphate phosphatase gene AtTPPI can improve root architecture, and tppi1 mutants have significantly shortened primary roots. However, the mechanism underlying the short roots of the tppi1 mutant and the upstream signaling pathway and downstream genes regulated by AtTPPI are unclear. Here, we demonstrated that the AtTPPI gene could promote auxin accumulation in AtTPPI-overexpressing plants. By comparing the transcriptomic data of tppi1 and wild-type roots, we found several upregulations of auxin-related genes, including GH3.3, GH3.9 and GH3.12, may play an important role in the AtTPPI gene-mediated auxin transport signaling pathway, ultimately leading to changes in auxin content and primary root length. Moreover, increased AtTPPI expression can regulate primary root growth and lateral root elongation under different concentration of nitrate conditions. Overall, constitutive expression of AtTPPI increased auxin contents and improved lateral root elongation, constituting a new method for improving the nitrogen utilization efficiency of plants.